Analysis of Stock Market Indices and Regimes on Commodity Markets - Kuchina, Elena; Cahlík, Tomáš, 1956-; Máša, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
The thesis focuses on the identification of the typical scenarios of the mutual relations among the stock markets considering different regimes on the commodity markets. For the identified scenarios the investment recommendations have been suggested. Considering different regimes the commodity markets go through and the mutual linkage among the stock markets during different situations on the commodity markets, six scenarios of the stock markets' mutual relations have been analyzed. It was shown that during most unstable period, when highly volatile regime prevails simultaneously on the energy, precious metals and non-energy commodity markets, the whole economy becomes to be more tied: the stock market indices demonstrate stronger interdependence, and as a consequence the benefits of diversification begin to fail. During the simultaneous presence of low volatility on all three analyzed commodity markets the agreement between occurrences of highly volatile state of most stock markets, besides the indices within the European region (DAX, CAC 40, IBEX 35), is rather weak. Similarly the correlation within regions and with other regions is weaker comparing with other situations on the commodity markets, so the standard investment strategy can be kept. It was also shown that the interdependence among the stock markets during the period of high volatility on the energy market differs depending on the source underlying the oil price shocks causing higher volatility. The regimes prevailing on the commodity and stock markets during different time periods have been detected by applying Hidden Markov Model methodology. To examine the similarity between the stock market indices in terms of highly volatile regimes' occurrences, Jaccard's similarity coefficient is employed. The correlation among the stock markets was computed by Spearman correlation coefficient.
The final part of research is devoted to the model-based approach used to analyze the dependence of the movement direction of SSEC index on other stock market indices between two trading days during different situations on the commodity markets. The dependency analysis was performed by applying Stochastic Gradient Boosting methodology.
Vedoucí práce: Tomáš Cahlík
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor disert. práce]; disertace; dissertations